KOMUNIKASI PEMASARAN WAHANA CIPTA SINATRIA DALAM MENDUKUNG DESA WISATA SUMBERBULU, KECAMATAN MOJOGEDANG, KABUPATEN KARANGANYAR - Raharjo, Valentino Bimo; Kusumo Aji, Haryo; Widiyowati, Estu (Solidaritas, 2024)
This research was conducted with the aim of knowing and describing the marketingcommunication of the Wahana Cipta Sinatria (WCS) Homestay towards the SumberbuluTourism Village. The researcher used a qualitative descriptive method to understand thephenomenon and obtain in-depth data holistically regarding the marketingcommunication of the Wahana Cipta Sinatria Homestay towards the SumberbuluTourism Village through the application of IMC (Integrated Marketing Communication)by Schultz. Data collection techniques include observation, interviews anddocumentation. Based on the results of the research analysis, Wahana Cipta Sinatria(WCS) carries out integrated marketing communications or IMC (Integrated MarketingCommunication), including advertising, sales promotion, personal selling, publicrelations, direct marketing. The conclusion of this study is that Wahana Cipta Sinatria(WCS) implements IMC (Integrated Marketing Communication) marketingcommunications, including the use of social media such as WhatsApp, Instagram andFacebook in conducting promotions, interacting directly with visitors through personalselling, building public relations activities in marketing and sponsorship activities andconducting direct marketing to build trust and fedback.Keywords: Wahana Cipta Sinatria, Marketing Communication, IMC